2021
DOI: 10.2147/ccide.s319631
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Hydroxyapatite Toothpaste to Prevent Root Caries: A pH-Cycling Study

Abstract: The effectiveness of a hydroxyapatite (HAP) toothpaste and a fluoride toothpaste in preventing root tissue demineralization (root caries) was compared using an established pH-cycling caries model. Materials and Methods: Sixty dentin blocks were produced from the root tissue of extracted human teeth and were assigned to 3 test groups (n=20/group): 10% hydroxyapatite toothpaste (HAP), 1450 ppm fluoride toothpaste (fluoride), and artificial saliva (artsaliva). Early root caries lesions were developed in each samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…The biomimetic active ingredient hydroxyapatite is used in various fields of oral care [ 7 , 14 , 15 , 16 , 18 , 103 ]. It remineralizes early caries lesions [ 104 , 105 , 106 , 107 ], reduces the initial bacterial attachment to enamel similar to 0.2% chlorhexidine [ 19 ], and acts as buffer and a calcium and phosphate reservoir in biofilms [ 108 ]. To extend these preventive effects, hydroxyapatite can be used together with lactoferrin, xylitol, zinc, allantoin, bisabolol, and/or hyaluronic acid to achieve an antibacterial effect and to prevent/reduce gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…The biomimetic active ingredient hydroxyapatite is used in various fields of oral care [ 7 , 14 , 15 , 16 , 18 , 103 ]. It remineralizes early caries lesions [ 104 , 105 , 106 , 107 ], reduces the initial bacterial attachment to enamel similar to 0.2% chlorhexidine [ 19 ], and acts as buffer and a calcium and phosphate reservoir in biofilms [ 108 ]. To extend these preventive effects, hydroxyapatite can be used together with lactoferrin, xylitol, zinc, allantoin, bisabolol, and/or hyaluronic acid to achieve an antibacterial effect and to prevent/reduce gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride-free prophylactic systems have been investigated in the last decade. It has been shown that they can be as efficient as fluoride-containing systems to prevent dental caries [ 8 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Thus, they may present a viable alternative to fluoride-containing agents in oral care.…”
Section: Discussionmentioning
confidence: 99%
“…Karex toothpaste with a 10% hydroxyapatite has been proven by the study by the authors B. T. Amaechi et al, as an effective toothpaste in the control of root caries, which is an alternative in its management compared to toothpastes containing sodium fluoride [60]. However, E. Paszynska et al claim that hydroxyapatite has a high biocompatibility and, if it is accidentally swallowed by children, it is safe.…”
Section: Remineralization Of Dental Enamelmentioning
confidence: 99%